Risk Analysis of Ship Repair Process Delays Using the Failure Mode and Effects Analysis (FMEA) Method - Syiam Laksono Harmawanto; Intan Baroroh (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
The ship repair process in shipyards is highly complex and prone to delays due to various technical, managerial, and workplace environmental factors. PT XYZ, a company engaged in ship repair, continues to experience delays in project completion, adversely affecting company performance and shipowner satisfaction. This study aims to identify the risk factors contributing to delays in ship repair processes, determine risk priorities, and develop effective mitigation strategies. The Failure Mode and Effects Analysis (FMEA) method was employed, with data collected through observations, interviews, and questionnaires involving relevant parties in the ship repair process. The risks were assessed based on Severity, Occurrence, and Detection ratings to calculate the Risk Priority Number (RPN), supported by risk-matrix mapping. The results show that risks were identified across five categories of ship repair work: replating, piping, painting, welding, and safety-equipment maintenance. The risks with the highest RPN values were schedule changes caused by additional work (RPN = 28.07) and damage to safety equipment resulting from the absence of routine functional testing (RPN = 22.75). The study concludes that FMEA is effective in identifying and prioritizing delay risks in ship repair processes. Implementing structured mitigation strategies is expected to minimize work delays while improving the quality and safety of ship repair activities at PT XYZ.